2022
DOI: 10.3390/cancers14205155
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Computed Tomography Scanning Protocols for Online Adaptive Proton Therapy of Head-and-Neck Cancers

Abstract: Purpose: To evaluate the suitability of low-dose CT protocols for online plan adaptation of head-and-neck patients. Methods: We acquired CT scans of a head phantom with protocols corresponding to CT dose index volume CTDIvol in the range of 4.2–165.9 mGy. The highest value corresponds to the standard protocol used for CT simulations of 10 head-and-neck patients included in the study. The minimum value corresponds to the lowest achievable tube current of the GE Discovery RT scanner used for the study. For each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…While daily adaptation was used in this work as a proof of principle, it has been demonstrated that OAR sparing was comparable using daily and weekly OAs (Bobić et al 2021 ), suggesting that similar NTCP reductions as the one obtained in this study could be achieved using less frequent adaptations. Similarly, our results are expected to be representative of what would be achieved using CT-on-rails instead of scatter corrected CBCT as in-room imaging modality, since both were shown to provide clinically equivalent results in the context of head and neck online adaptive proton therapy (Nesteruk et al 2021 , 2022 ).…”
Section: Discussionsupporting
confidence: 53%
“…While daily adaptation was used in this work as a proof of principle, it has been demonstrated that OAR sparing was comparable using daily and weekly OAs (Bobić et al 2021 ), suggesting that similar NTCP reductions as the one obtained in this study could be achieved using less frequent adaptations. Similarly, our results are expected to be representative of what would be achieved using CT-on-rails instead of scatter corrected CBCT as in-room imaging modality, since both were shown to provide clinically equivalent results in the context of head and neck online adaptive proton therapy (Nesteruk et al 2021 , 2022 ).…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, we expect our results to be representative of using CT-on-rails instead of scatter-corrected CBCT for in-room imaging of the patient in the treatment position. Recent studies have shown that both modalities provide clinically equivalent results for adaptive proton therapy of head-andneck cancers [27,29].…”
Section: Discussionmentioning
confidence: 99%
“…We considered eight H&N patients initially treated with volumetric modulated arc therapy (VMAT) at the Massachusetts General Hospital between August 2019 and August 2021 because CBCT imaging was unavailable for our proton patients. Note that this patient cohort differs from the one in our previous studies [23,24,27,29] in that these patients required full offline replanning during their treatment due to large anatomical changes caused by weight loss, clinical target volume (CTV) shrinkage, or a combination of both. Table 1 summarizes the patient cohort, reflecting the observed weight and CTV size changes throughout the treatment.…”
Section: Patient Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity of DIR algorithms to image noise, resolution (Constable and Henkelman 1991 , Verdun et al 2015 , Zhao et al 2016 , Sarrut et al 2017 ), field of view (Barber et al 2020 ) and image contrast (Mencarelli et al 2014 , Barber et al 2020 , Dowling and O’Connor 2020 ) has been demonstrated in the literature. However, other studies find that the effect of image noise has only minor effects on DIR results for computed tomography (CT) to CT registrations (Nesteruk et al 2022 ).…”
Section: Source Of Uncertaintiesmentioning
confidence: 99%